Analisis Modal Kerja Dan Pengelolaan Keuangan Terhadap Pendapatan Usaha Mikro Kecil Dan Menengah (UMKM) Bakso “Yanto KPN” Di Kota Serang - Deni Sunaryo; Hamdan Hamdan; Adi Sucipto (Journal Of Business, Finance, and Economics (JBFE), 2023)
This research aims to determine and analyze the influence of Working Capital and Financial Management on the Income of Micro, Small and Medium Enterprises (MSMEs) Case Study of the "Yanto KPN" Meatball UMKM. To obtain data from these variables, researchers made direct observations at the "Yanto KPN" Meatball UMKM. The data used in this research is primary data. This type of research uses action research with a case study method. The data collection techniques used were interviews, observation and documentation. The method used in this research is Multiple Linear Regression Analysis, Classical Assumption Test and Hypothesis Testing using the SPSS program. Based on the results of the T test in this research, it shows that working capital has a positive and significant effect on income, and financial management also has a positive and significant effect on income. Simultaneous results with the F test in this study show that working capital and financial management simultaneously have a positive and significant effect on income. The R Square (R2) value is 0.650, which indicates that 65% of income can be explained by independent variables, namely working capital and financial management, while the remaining 35% is explained by other variables. It is recommended that Bakso "Yanto KPN" MSMEs pay more attention to working capital and financial management in a systematic way to make it easier to evaluate working capital and financial management as well as respondents' openness in answering researchers' questions.